Ethical codes of conduct and practices using human subjects - Mohd.Salleh, Norani; Mohd.Saata, Rohaida (Procedia, social and behavioral sciences, 2010)
The objective of this exploratory study is to understand lecturers’ perception of ethics as it relates to the use of human subjects. Voluntary participation, protection from risks and cultural sensitivities are issues highlighted. Ten research course lecturers who were in-charge of academic research were interviewed. Study shows that lecturers are conversant with ethical procedures. However lack of clear ethical guidelines and enforcement mechanism promotes several scenarios; those who adhered to specific codes of ethics completely; those who are unfussy and viewed the matter as institutional prerogatives, and those who weight expediency more. Personal academic experiences abroad underscored their stances.